2011
DOI: 10.1016/j.envpol.2011.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pollution in tropical rivers (Guadeloupe): Role of ecological factors in food web bioaccumulation

Abstract: This paper determines the bioaccumulation and transfer processes of organochlorine pesticides within the stream food web in Guadeloupe (Caribbean). ABSTRACTConcentrations of organochlorine pesticides and stable isotope ratios of nitrogen and carbon were measured in a tropical freshwater ecosystem to evaluate the contamination level of biota and examine the bioaccumulation patterns of pollutants through the food web. Chemical analyses showed a general and heavy contamination of the entire food web. They reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 28 publications
3
75
0
2
Order By: Relevance
“…This result is in agreement with previous studies highlighting the CLD concentration in different organisms. Indeed, Van Veld et al (1984) demonstrated that CLD could be accumulated in the channel catfish when exposed for 30 days, and Coat et al (2011) observed the CLD bioaccumulation in tropical food web including various species of mussels, shrimps and fishes. The CLD concentrations measured in muscle tissue of M. rosenbergii were somewhat lower than those measured in other decapods exposed to similar CLD concentrations Gaume et al, 2014).…”
Section: Chlordecone Bioaccumulationmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in agreement with previous studies highlighting the CLD concentration in different organisms. Indeed, Van Veld et al (1984) demonstrated that CLD could be accumulated in the channel catfish when exposed for 30 days, and Coat et al (2011) observed the CLD bioaccumulation in tropical food web including various species of mussels, shrimps and fishes. The CLD concentrations measured in muscle tissue of M. rosenbergii were somewhat lower than those measured in other decapods exposed to similar CLD concentrations Gaume et al, 2014).…”
Section: Chlordecone Bioaccumulationmentioning
confidence: 99%
“…Although, Fernández-Bayo et al (2013) showed the existence of CLD degrading organisms in a tropical soil (andosol) microcosm under aerobic conditions, CLD undergoes no significant or quick biotic or abiotic degradation (Dolfing et al, 2012;Levillain et al, 2012). Driven by the water cycle, CLD in soils is progressively transferred to aquatic ecosystems (Coat et al, 2011) and also in the food web because of its high K oc (Soil Organic Carbon Water Partitioning Coefficient) (15849 L/Kg), K ow (Octanol-Water Partition Coefficient) (4.5-6.0) and its affinity for lipids (Cabidoche and Lesueur-Jannoyer, 2012;Clostre et al, 2013;Sterrett and Boss, 1977;UNEP, 2005;US-EPA, 2008). Human contamination has also been detected in FWI population mainly resulting from consumption of contaminated food, seafood and root vegetables (Dubuisson et al, 2007;Gaume et al, 2014;Guldner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current tacit assumption is that the presence of this compound is not the result of a biotic or abiotic dechlorination of CLD in these matrices but rather the consequence of its presence as an impurity, a by-product of its preparation, in the CLD released in the environment (Borsetti and Roach 1978;Cabidoche et al 2009;Coat et al 2011;Martin-Laurent et al 2014). Until now, however, this assumption could not be verified since no detailed chemical analyses of the CLD commercial formulations (and so of their 5b-hydroCLD content) seem to exist in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…5b-Hydrochlordecone 4 (5b-hydroCLD), whose structure is identical to CLD except that one chlorine atom is replaced by a hydrogen at position 5b (Chemical Abstracts Service (CAS) numbering) and which is commercially available as an analytical standard, has been searched for and often detected in environmental matrices (soil, surface water and groundwater, sediments, plants, avian tissues and eggs, crustaceans, molluscs and fishes) from the geographical areas where CLD was applied (FWI) or unintentionally released during its manufacture (USA) (Borsetti and Roach 1978;Harless et al 1978;Stafford et al 1978;Carver and Griffith 1979;Orndorff and Colwell 1980;Coat et al 2011;Martin-Laurent et al 2014;Clostre et al 2014a, b). The current tacit assumption is that the presence of this compound is not the result of a biotic or abiotic dechlorination of CLD in these matrices but rather the consequence of its presence as an impurity, a by-product of its preparation, in the CLD released in the environment (Borsetti and Roach 1978;Cabidoche et al 2009;Coat et al 2011;Martin-Laurent et al 2014).…”
Section: Introductionmentioning
confidence: 99%